Effects of Renal Impairment on the Pharmacokinetics of Gefapixant, a P2X3 Receptor Antagonist. (7th July 2022) - Nussbaum, Jesse C.; Hussain, Azher; Min, K. Chris; Marbury, Thomas C.; Lasseter, Kenneth; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Gefapixant, a P2X3 receptor antagonist, has demonstrated efficacy in patients with refractory or unexplained chronic cough. We investigated the effect of renal impairment (RI) on the pharmacokinetics (PK) of gefapixant 50 mg in an open‐label, single‐dose study enrolling participants with moderate (n = 6) or severe (n = 6) RI, end‐stage renal disease (ESRD; n = 6) under hemodialysis (HD) and non‐HD conditions, and healthy matched controls (n = 6). Serial plasma and urine samples for gefapixant concentrations were collected at selected time points over 72 and 48 hours after dosing, respectively. Linear regression analysis predicted a 1.87‐, 2.79‐, and 3.76‐fold higher exposure (area under the plasma concentration–time curve) for participants with mild, moderate, and severe RI, respectively, than that for healthy matched control participants. Categorical analysis exhibited a 2.98‐, 4.43‐, and 4.74‐fold higher exposure for participants with moderate RI, severe RI, and ESRD, respectively, than that for healthy matched control participants. Apparent oral clearance and renal clearance was lower in participants with various degrees of RI, by 66% to 90%, compared with healthy matched control participants, explaining the increased gefapixant exposure with increasing degrees of renal impairment. Gefapixant area under the plasma concentration–time curve and maximum plasma concentration decreased by ≈25% under HD conditions compared to non‐HD conditions. Single‐dose administration of gefapixant was generally well tolerated in this study. The data from this trial informed the enrollment of phase 3 clinical trials that evaluated the efficacy and safety of gefapixant in >2000 participants with refractory or unexplained chronic cough. Those efficacy and safety data, combined with analysis of population pharmacokinetics from across the entire development program, will be used to evaluate the magnitude of the renal impairment effect in the refractory or unexplained chronic cough population and to determine any dose adjustment recommendations.